In vivo protein-DNA interactions at hypersensitive site 3 of the human beta-globin locus control region. - Strauss, E C (1992)
The expression of beta-globin genes in developing erythroid cells is dependent on distant, upstream regulatory sequences, known as the locus control region (LCR), which are marked in chromatin by DNase I hypersensitive sites (HS-1 to HS-4). Linkage of the beta-globin gene complex LCR or fragments surrounding core regions of 200-300 base pairs to the human beta-globin gene permits consistent, high-level expression of the transgene in mice. To define the array of nuclear factors interacting with beta-LCR HS-3, we have performed in vivo dimethyl sulfate footprinting of the active HS-3 core in erythroid cells by a modified procedure that permits assessment of protein-DNA contacts at adenine, as well as guanine, residues. In vivo protein occupancy differs considerably from that predicted from previous in vitro binding analyses. In vivo footprinting detects protein binding at four sites recognized by the erythroid transcription factor GATA-1, at two CACC/GT motifs, and at a single AP-1/NF-E2 site. The regulatory elements occupied in vivo in HS-3 appear similar to those described previously in globin gene promoters and 3' enhancers. These findings suggest that the distinctive properties of the HS-3 region may be attributable to the organization of these occupied motifs and the consequent protein interactions, rather than to the binding of unique LCR regulatory factors.